Prevalence and Risk for Bundle Branch Block, Atrioventricular Block and Pacemaker Implantation in Spondyloarthritis. A Systematic Review of the Literature - Park, Hye Sang; Laiz, Ana; Díaz del Campo, Petra; Martín Martínez, María A.; Guerra-Rodriguez, M.; Alonso-Martin, Concepcion; Sanchez-Vega, Jesus; Corominas, Hector (Frontiers in Medicine, 2022)
Objective: To evaluate the evidence regarding the prevalence and risk of bundle branch block (BBB), atrioventricular block (AVB) and pacemaker implantation (PMI) in patients with spondyloarthritis compared to a control group without spondyloarthritis. Methods: A systematic review of the literature was performed using Pubmed (Medline), EMBASE (Elsevier) and Cochrane Library (Wiley) databases until December 2021. The prevalence and risk for AVB, BBB and PMI were analyzed. Cohort, case control and cross-sectional studies in patients ≥18 years meeting the classification criteria for spondyloarthritis were included. The Odds ratio (OR), risk ratio (RR), or Hazard ratio (HR) and prevalence difference were considered as outcomes. Data was synthesized in a previously defined extraction form which included a risk of bias assessment using the Newcastle-Ottawa Scale. Results: In total, eight out of 374 studies were included. Regarding low grade AVB and BBB indirect results comparing prevalences were found. According to population based registries, the sex and age adjusted HR of AVB was 2.3 (95% CI 1.6 - 3.3) in ankylosing spondylitis, 2.9 (95% CI 1.8 - 4.7) in undifferentiated spondyloarthritis and 1.5 (95% CI 1.1 a 1.9) in psoriatic arthritis. The absolute risk for AVB was 0.4% (moderate to high; 95% CI 0.34%-0.69%) for AS, 0.33% (moderate to high; 95% CI 0.21%-0.53%) for uSpA and 0.34% (moderate to high; 95% CI 0.26%-0.45%) for PsA.The RR for PMI in AS patients was 1.3 (95% CI 1.16 - 1.46) for groups aged between 65-69 years, 1.33 (95% CI 1.22 - 1.44) for 70-75 years, 1.24 (95% CI 1.55 - 1.33) for 75-79 years and 1.11 (95% CI 1.06 - 1.17) for groups older than 80 years. Conclusions: No study evaluated association measures for low grade AVB and BBB but the differences of prevalence were similar in SpA and control groups. According to population based registries there was an approximately two fold-increased risk of high grade AVB in SpA patients. RR for PMI was higher in younger age groups.